Organising care around patients Stories from the frontline of the NHS - Chambers, Naomi (Manchester University Press, 2021)
Healthcare aims to be patient-centred but a large gap remains between the fine words and the reality. Care often feels designed for the convenience of the organisations that deliver it, and not enough around patients and their families, or even around the frontline staff who provide it. Why does this happen? What does it feel like? What can be done about it? This book stimulates reflection on these questions by listening closely to those at the frontline. It provides accounts from patients, carers and healthcare professionals who are patients about what it's like when services get it right, and wrong, from birth up to the end of life. Quite simply, we want to draw upon the power of storytelling - which is increasingly valued as a tool for learning - to help policymakers and practitioners to understand how to deliver better care. We also hope to enlighten the general reader about how they might go about navigating "the system" while it remains imperfect. There is a growing literature of first-person accounts from patients and from healthcare professionals. This book differs by providing a collection of narratives of experiences of the NHS in England to paint a rich and varied picture. Alongside these narratives we provide some international context, and an overview of the history of moves towards a more patient-centred approach to care. We present the theory and practice of storytelling in the context of healthcare. We also seek to help the reader to draw out the practical learning from the individual accounts.